PELATIHAN PEMBUATAN MATERI DAN EVALUASI UNTUK MENINGKATKAN KETERAMPILAN GURU DALAM ADAPTASI GAMIFIKASI - Mustika, Nur; Kamaruddin, Kamaruddin; Alam, Syamsu; Aeni, Zahratul (LPPM Universitas Bina Bangsa, 2024)
The 1945 Constitution mandates the state to enhance public intelligence, with teachers being central to educational quality. UPT SPF SD Inpres Rappokalling 2 in Makassar faces a decline in student engagement, attributed to teachers' insufficient skills in using technology for interactive teaching and assessment. To address this issue, a community service program was implemented, involving training and mentoring with Canva and Wordwall. Evaluation results from pre-tests and post-tests showed significant improvement in teachers' knowledge and skills. Proficiency in creating teaching materials using Canva increased from 59% to 68%, while the ability to create assessments using Wordwall rose from 76.25% to 90%. This enhancement is expected to make teaching materials and assessments more engaging and effective, thereby supporting increased student involvement in the learning process